Der Trafikant - Piirainen, Notburga (2020)
The basis of this master thesis is the novel The Tobacconist from Robert Seethaler. The protagonist of the novel is the seventeen-year-old Franz who has to move from the countryside to Vienna, because of financial reasons, in order to become a tobacconist. The narrative takes place in the years of 1937/38 when Germany annexes Austria and the world is only footsteps away from war. It is during that time that Franz has to grow up. The research questions are: - In what way do other characters in the novel influence the process of Franz's growing up? - How do the events described in the novel relate to Franz's maturation process on the path of growing up? The chosen research method is the literary analysis research method, in which elements of the qualitative content analysis are used, such as coding, which means the classification of the created categories into part of the research material. In this master thesis parts of the research material are citations taken from the novel.